Studi Hubungan Self-Efficacy terhadap Hasil Belajar Kognitif pada Mahasiswa PGSD Surakarta UNS - Elvina Isna Nurjanah; Matsuri Matsuri; Roy Ardiansyah (Didaktika Dwija Indria, 2023)
This research aims to find out whether there is a relationship between the self-efficacy variable and the cognitive learning outcome variable. The research design taken is correlational research with data collection techniques in the form of tests and scales. The research population is the entire student PGSD UNS Forces 2021. Sampling is done using the random cluster sampling technique. The data analysis technique used is simple correlation coefficient analysis. From the results of data analysis can be drawn the conclusion that there is no positive and significant relationship between self-efficacy and cognitive learning outcomes with the acquisition of a significance value of 0,657 > 0,05 with a pearson correlation value of -0,054.